The Clay bird - Masuda, Tareka; Masuda, Kyatharina; Bablu, Nurul Islam; Farazi, Russell; Chattopadhyay, Jayanto; Prachy, Rokeya; MK2 Productions; Milestone Film & Video; New Yorker Video (Firm) ([Harrington Park, NJ] : Dhaka : Milestone Film & Video ; MK2 : TF1 Video, [New York] : Distributed by New Yorker Video, 2006)
Set against the backdrop of Pakistan during the turbulent 1960s, a family is ripped apart by religious beliefs and civil war. A young boy from Bangladesh is sent away by his Muslim father to a Madrasah. He struggles to adapt to a harsh monastic life.
Title from container.
Originally released as a motion picture in 2002.
Special features: The making-of 'The clay bird' video documentary; Video interviews with the cast and crew; Theatrical press kit downloadable on DVD-ROM; Three songs from the soundtrack; Stills gallery; French and American theatrical trailers.
Nurul Islam Bablu, Russell Farazi, Jayanto Chattopadhyay, Rokeya Prachy.
DVD, region 1; Dolby Digital.
Bengali dialogue, English subtitles.
Keywords: Boys -- Bangladesh -- Drama; Monastic and religious life -- Drama; Feature films; Foreign films; Historical films; Historical -- Feature; Historical films